Towards political equality in the context of participatory and deliberative democratic theory - Železnik, Ana (Teorija in praksa, 2017)
Modern democracy needs citizens, but citizenship has become a complex concept owing to the changes that digital media and social platforms have brought to political participation and civic engagement, which political institutions can no longer ignore. This article questions the way political parties conceive of digital citizenship and how they incorporate new media into their own communication practices. While changes in civic engagement and political participation are most prevalent among young people, the primary focus of this article is the problem of how political parties represent young people as emerging citizens and their potential future voters. Our study uses recent research on young citizens and the responses of political parties to young citizens to provide answers. We also perform a qualitative analysis of their representatives within a sample of Slovenian political parties. The aim of the article is to present a general map of youth as an emerging citizenry within the digital culture in order to identify the problems political parties are facing in their inability to identify with young people as digital citizens.
Keywords: Civil society; Civilna družba; Deliberative democracy; Enakost; Equality; Mladina; Political participation; Political parties; political party; Politična participacija; Politične stranke; Posvetovalna demokracija; Slovenia; Slovenija; Youth